The Arabic grammar syllabus at bachelor level: an analytical study - Dollah, Nafi@Hanafi (2004)
Issues and Methodologies The Arabic Grammar Syllabus at Bachelor Level.An Analytical Study on Current Trends on Teaching Arabic language and Literature